Literature Review: Efektivitas Art Therapy untuk Meningkatkan Self-Compassion pada Orang Dengan HIV/AIDS - Madidar, Sophie Maylinda; Muhid, Abdul (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2021)
In dealing with the level of self-compassion in ODHA and how effective Art Therapy is in increasing self-love in good or bad conditions, is the formulation of the problem that is used as the basis for this literature review. HIV is a dangerous threat to human health starting from physical health, social conditions, and psychological conditions. This can cause low self-compassion in some people. This can beobserved through negative behaviors that are carried out on himself. Compassion is very important in human life, because compassion can be a supporting element of one's well-being. Art Therapy is a therapy that is said to be effective in dealing with psychological problems, can increase the level of individual self-quality and also has the potential to increase self-compassion. So what are the steps taken to assess the effectiveness of Art Therapy in an effort to increase self-compassion in ODHA. Self-compassion can be measured by the Self Compassion Scale (SCS). The method used in this literature study is using existing research to analyze and find answers to the previous problem formulation. It can be seen that previous researchers have proven the effectiveness of Art Therapy in an effort to increase the level of self-compassion in people with HIV/AIDS (ODHA).